Sedimentary environments in the south-western Barents Sea during the last deglaciation and the Holocene: a case study outside the Ingøydjupet trough - Mauro Pau; Øyvind Hammer (Polar Research, 2016)
A lithological and foraminiferal study of newly acquired sediment cores outside the Ingøydjupet (Ingøy Deep) trough has been carried out to improve constraints on the last deglacial history in the south-western Barents Sea. Three lithofacies and three foraminiferal facies were identified. The lowermost lithological unit is a diamicton interpreted as glacial till. It contains a low-abundance, ecologically mixed foraminiferal assemblage, presumably resulting from glacial reworking. Above the diamicton, a layer of ice-rafted debris (IRD), likely associated with intensive iceberg production, marks the initial destabilization of the marine-based ice sheet. At this time, ca. 15.6–15.0 Ky B.P., opportunistic foraminiferal species Nonionellina labradorica and Stainforthia spp. reached peak abundance. During the south-western Barents Sea ice-margin retreat, presumably corresponding to the Bølling interstadial, a sequence of glaciomarine laminations was deposited conformably on the layer of IRD. Sedimentation rates were apparently high (estimated about 0.4 cm per year) and the foraminiferal fauna was dominated by Elphidium spp. and Cassidulina reniforme, species common for glacier-proximal environments. A hiatus at the top of the deglacial unit is likely linked to the high bottom-current activity associated with a strengthened inflow of Atlantic water masses into the Barents Sea. The uppermost lithological unit is represented by the Holocene marine sandy mud. It contains a high-abundance, high-diversity foraminiferal fauna with common cassidulinids, Cibicides spp., Epistominella pusilla and planktic species.